Pengaruh Ukuran Kap dan Audit Fee Terhadap Auditor Switching dengan Tingkat Pertumbuhan Perusahaan Klien sebagai Variabel Moderasi - Meita Margaretha; Budi Kurniawan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The research aims to test the impact of the size kap and audit fee on auditors switching with the rate of growth of client companies as moderation variables. The population in this study is the entire infrastructure, utility and transport companies registered at the Indonesia stock exchange in 2015-2019. The number of samples used in this study is 25 companies with sample samples sampling techniques and the number of research data observations obtained at 125. Data analysis methods are done with regression and moderated regression analysis (mra). Research has concluded that the size of the bonnet effect positive on the auditors switching and the audit fee reflects negative on the auditors switching. The rate of growth for corporate clients was unable to modernize the oversize of the hoods and the audit switching auditors.